2008
DOI: 10.1002/cbic.200800617
|View full text |Cite
|
Sign up to set email alerts
|

Metal Binding Properties of Fluorescent Analogues of Trichogin GA IV: A Conformational Study by Time‐Resolved Spectroscopy and Molecular Mechanics Investigations

Abstract: The metal ion binding properties of two fluorescent analogues of trichogin GA IV, which is a natural undecapeptide showing significant antimicrobial activity, were studied by circular dichroism, time-resolved optical spectroscopy, and molecular mechanics calculations. Binding of Ca(II) and Gd(III) to the peptides investigated was shown to promote a structural transition from highly helical conformations to folded structures characterized by formation of a loop that embedded the metal ion. Time-resolved spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
5
21
0
Order By: Relevance
“…We already reported similar experiments concerning the interaction of F0TrOMe with Gd(III) and Ca(II) ions, which showed the same behavior as that of Tb(III) ions . Interestingly, the titration with the Gd(III) ions produced a positive CD band very similar in shape and intensity to the corresponding band recorded for the F0TrOMe/Tb(III) ion complex.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We already reported similar experiments concerning the interaction of F0TrOMe with Gd(III) and Ca(II) ions, which showed the same behavior as that of Tb(III) ions . Interestingly, the titration with the Gd(III) ions produced a positive CD band very similar in shape and intensity to the corresponding band recorded for the F0TrOMe/Tb(III) ion complex.…”
Section: Resultssupporting
confidence: 69%
“…The dynamics of a conformational transition from an elongated, helical conformation to a family of compact, folded structures, for some Trichogin analogs was characterized by us some years ago, by use of theoretical conformational analysis and time‐resolved spectroscopic studies . We have also found that in these fluorescent TrGA analogs the conformational transition from an essentially helical structure to a turn conformation may be triggered by the binding of Ca(II) and the lanthanide Gd(III) ions …”
Section: Introductionmentioning
confidence: 99%
“…According to the MD calculations, the conformation switch takes place at the level of the –Gly 5 –Gly 6 – dipeptide, already known to be fairly flexible . The lowest energy (33.72 kcal/mol) 3 D structure is shown in Figure .…”
Section: Resultssupporting
confidence: 69%
“…However, the MD results indicate that, in the case of trichogin, membrane thinning might be driven also by specific interactions between the peptide N-and C-termini and the phospholipid headgroups. In this respect, it is important to note that we have previously shown that in solvents of low polarity trichogin binds cations with a very high affinity [142]. This result might reflect …”
Section: Discussionmentioning
confidence: 84%
“…A well characterized, medium-length peptaibiotic is GAIV, whose sequence is nOct -Aib 1 -Gly 2 -Leu 3 -Aib 4 -Gly 5 -Gly 6 -Leu 7 -Aib 8 -Gly 9 -Ile 10 -Lol, where nOct is n-octanoyl, and Lol is leucinol. This 10-mer peptide was isolated from Trichoderma longibrachiatum in 1992 [6] and since then it was studied both in solution and in model membranes by a number of physico-chemical techniques [108] including NMR [6,54], X-ray crystallography [137], EPR [88-90, 114, 130, 131] fluorescence [45,86,126,[140][141][142] electrochemistry [10,123], and molecular dynamics (MD) simulations [17]. Its 3D-structure is helical, with a flexible hinge in the central part, formed by two consecutive Gly residues [6,137,138,141].…”
Section: Trichogin Gaivmentioning
confidence: 99%